Berbagi Pengetahuan tentang Kinerja Karyawan Melalui Mediasi dan Inovasi Kerja (Sharing Knowledge on Employee Performance Through Mediation and Work Innovation) - Liana, Yuyuk; Romlah, Siti; Erawati, Sherly Hesti; Irawati, Rina; Rachmania, Benita (Akutansi Bisnis & Manajemen ( ABM ), 2025)
This study aims to examine the effect of knowledge sharing on employee performance with work innovation as a mediating variable. The quantitative methodology used in this investigation involves distributing cross-sectional surveys to 60 employees in Lenteng Regency, Sumenep Regency. Partial Least Square is used in structural equation modeling and model evaluation of the collected data. The data processing process in this study uses Smart PLS 3 software. Statistical analysis shows that knowledge sharing directly and indirectly affects performance. The findings of this study offer insight for employees in Lenteng Regency, Sumenep Regency to emphasize the importance of knowledge sharing in improving performance. This underscores the need for sub-district institutions to formulate more comprehensive regulations that promote that knowledge sharing is beneficial to all stakeholders and has a positive impact on performance.